Assessment of the strategies adopted by teachers in the teaching of science from the perspective of basic education students (2018)
Objective: to characterize and assess the level of development in pedagogical competences through the strategies adopted by Basic Education teachers in the teaching of science from the students’ perspective. Methodology: A quantitative approach was applied which was of a descriptive and multifactorial nature. The data was collected among the eighth and ninth grade students of the Santiago Apóstol Educational Institution, municipality of Santiago, Norte de Santander, Colombia. A Likert scale was used for students to describe the pedagogical practice of teachers in the area of Natural Sciences including the three aspects that are assessed in the development of pedagogical competence: curricular planning, curriculum development and curriculum assessment (monitoring and improvement). Results: the statistical tests show that teachers develop reflective pedagogical practices which require reinforcement in the Research Based Instructional Strategy (RBIS) and in Information and Communication Technologies (ICT) leading to the development of more assertive scientific competences. Conclusions: strategies were identified to foster the development of scientific competences in students and the use of didactic resources and laboratory practices, however, they are not articulated to the needs of students.